Supercapacitors on demand: all-printed energy storage devices with adaptable design. (19th February 2019) - Brooke, Robert; Edberg, Jesper; Say, Mehmet Girayhan; Sawatdee, Anurak; Grimoldi, Andrea; Åhlin, Jessica; Gustafsson, Göran; Berggren, Magnus; Engquist, Isak
Abstract: Demands on the storage of energy have increased for many reasons, in part driven by household photovoltaics, electric grid balancing, along with portable and wearable electronics. These are fast-growing and differentiated applications that need large volume and/or highly distributed electrical energy storage, which then requires environmentally friendly, scalable and flexible materials and manufacturing techniques. However, the limitations on current inorganic technologies have driven research efforts to explore organic and carbon-based alternatives. Here, we report a conducting polymer:cellulose composite that serves as the active material in supercapacitors which has been incorporated into all-printed energy storage devices. These devices exhibit a specific capacitance of ≈90 F g −1 and an excellent cyclability (>10 000 cycles). Further, a design concept coined 'supercapacitors on demand' is presented, which is based on a printing–cutting–folding procedure, that provides us with a flexible production protocol to manufacture supercapacitors with adaptable configuration and electrical characteristics.